β-secretase inhibition prevents structural spine plasticity deficits in AppNL-G-F mice - Blume, Tanja; Filser, Severin; Sgobio, Carmelo; Peters, Finn; Neumann, Ulf; Shimshek, Derya; Saito, Takashi; Saido, Takaomi C.; Brendel, Matthias; Herms, Jochen (Frontiers in Aging Neuroscience, 2022)
All clinical BACE1-inhibitor trials for the treatment of Alzheimer´s Disease (AD) have failed due to insufficient efficacy or side effects like worsening of cognitive symptoms. However, the scientific evidence to date suggests that BACE1-inhibition could be an effective preventative measure if applied prior to the accumulation of amyloid-beta (Aβ)-peptide and resultant impairment of synaptic function. Preclinical studies have associated BACE1-inhibition-induced cognitive deficits with decreased dendritic spine density. Therefore, we investigated dose-dependent effects of BACE1-inhibition on hippocampal dendritic spine dynamics in an APP knock-in mouse line for the first time. We conducted in vivo two-photon microscopy in the stratum oriens layer of hippocampal CA1 neurons in 3.5-month-old AppNL-G-FGFP-M mice over 6 weeks to monitor the effect of potential preventive treatment with a high and low-dose of the BACE1-inhibitor NB-360 on dendritic spine dynamics. Structural spine plasticity was severely impaired in untreated AppNL-G-FGFP-M mice, although spines were not yet showing signs of degeneration. Prolonged high-dose BACE1-inhibition significantly enhanced spine formation, improving spine dynamics in the AD mouse model. We conclude that in an early AD stage characterized by low Aβ-accumulation and no irreversible spine loss, BACE1-inhibition could hold the progressive synapse loss and cognitive decline by improving structural spine dynamics.